'People are fed up; don't mess with them.' Non-quantificational Arguments and Polarity Reversals. (3rd June 2022) - Chierchia, Gennaro
Abstract: The first sentence in the title means roughly: All the people around are tired. The second means: Do not mess with any of them. Even though the second sentence looks just like a negative counterpart of the first, it doesn't have the expected compositional meaning: it doesn't mean "do not mess with all the people". This phenomenon is extremely general. It takes place with Bare Plurals, as in the title. It figures prominently in the behavior of Plural Definites ( I spoke to the students in trouble ≅ ∀/ I didn't speak to the students in trouble ≅ ¬∃). It also takes place with Donkey pronouns ( Every farmer who had a donkey sold it ≅ ∀/ No man who had a donkey sold it ≅ ¬∃). These switches of quantificational force under polarity reversals call to mind Free Choice phenomena. In particular, a determiner like any is interpreted as a narrow scope existential in a sentence like I didn't talk to any student in trouble ≅ ¬ ∃; however, in positive environments, the existential meaning of any emerges as strengthened to universal I spoke to any student in trouble ≅ ∀. It is tempting to conjecture that the source of this uniform behavior is a uniform mechanism. While these constructions (Free Choice any, Bare Plurals, Plural Definites, and Donkey pronouns) have been studied extensively, and insightful approaches to Plural Definites in terms of Free Choice mechanisms have also been proposed (Bar Lev 2018, 2021 ), a unitary analysis has not been attempted to the best of my knowledge. In spite of the many challenges that a unified analysis faces, it is worth a try, for, if successful, it would considerably push forward our understanding of a wide range of very diverse constructions.